PELAYANAN PERPUSTAKAAN IPDN KAMPUS JAKARTA DI MASA PANDEMI COVID-19 - BOGA PRATALA (ACADEMIA: Jurnal Inovasi Riset Akademik, 2022)
The Library of IPDN Campus Jakarta is required to adapt in providing information services and reference sources to all academics during the Covid-19 pandemic. This article aims to describe the services provided by the Library of IPDN Campus Jakarta during the Covid-19 period. The method used is descriptive qualitative method, and literature study. The results of this study indicate that library services to the academic community during the Covid-19 period are still carried out face-to-face. The services provided include the use and search of library materials. Before the Covid-19 pandemic took place, the number of book borrowers and visitors of the Library of IPDN Campus Jakarta in 2017 to 2019 was still quite high. During the Covid-19 pandemic, the number of book borrowers and visitors of the Library of IPDN Campus Jakarta in 2020 to 2021 experienced a significant decline with the obstacles faced by the users of Library of IPDN Campus Jakarta who were unable to visit or borrow books directly (offline). To overcome the problem, a digital library system is needed at the Library of IPDN Campus Jakarta. ABSTRAKPerpustakaan Kampus IPDN Jakarta dituntut untuk beradaptasi dalam memberikan pelayanan informasi dan sumber referensi kepada seluruh sivitas akademika di masa pandemi Covid-19. Artikel ini bertujuan untuk mendeskripsikan pelayanan yang dilakukan Perpustakaan Kampus IPDN Jakarta selama masa Covid-19. Metode yang digunakan adalah metode kualitatif deskriptif, dan studi literatur. Hasil kajian ini menunjukkan bahwa pelayanan perpustakaan kepada sivitas akademika selama masa covid-19 ini tetap dilakukan secara tatap muka. Pelayanan yang diberikan meliputi pemanfaatan dan penelusuran bahan pustaka. Sebelum pandemi Covid-19 ini berlangsung, jumlah peminjam buku dan pengunjung Perpustakaan Kampus IPDN Jakarta pada tahun 2017 s.d 2019 masih cukup tinggi. Saat pandemi Covid-19 ini berlangsung, jumlah peminjam buku dan pengunjung Perpustakaan Kampus IPDN Jakarta pada tahun 2020 s.d 2021 mengalami penurunan yang signifikan dengan kendala yang dihadapi pengguna Perpustakaan IPDN Kampus Jakarta yang tidak dapat berkunjung atau meminjam buku secara langsung (offline). Untuk mengatasi ini, diperlukan sistem perpustakaan digital di lingkungan Perpustakan Kampus IPDN Jakarta.